“El mayor Señor que puede encontrarse”. Sobre la virtud de temer y hacerse temer en Maquiavelo - Morales Oyarvide, César (El Colegio de México A.C., 2023)
This article argues that among the set of emotions that populate the political landscape Machiavelli paints for his readers, fear is not only the most prominent, but the one most closely linked to virtù, the central concept of Machiavellian politics. Starting out from an analysis of the Florentine writer’s innovative conception of virtù, and following Pedullà, a bipartite classification is presented of the uses of fear in Machiavelli’s work: a “virtuous” use, leading to political success, and another that leads to ruin. Through a selection of passages from The Prince and the Discourses on Livy, the key examples of Machiavelli’s virtuous and non-virtuous uses of fear are traced, showing how the ability both to inspire and feel this emotion is linked to several of his most significant pieces of political advice.